Statistical concepts a basic program - Brown, Foster Lloyd (HarperCollins College, 1995)
Emphasizing practical applications, this text offers a programmed approach to learning fundamental statistics quickly and independently. Material is presented in short frames, each of which focuses on one concept or relationship and is followed by a question and answer that allows students to monitor personal progress. Three parallel columns are used as a guide to performing computations: the first provides formulas and pointers; the second provides examples of working and the third provides problems for students to solve. New computer quick start sections help students enter a few lines of instruction and a short data set into a computer to get a printed statistical analysis. MINITAB, SAS and SPSS are introduced. This text has also been updated to emphasize the importance of critical thinking in a statistical context and includes discussions of some common misuses of statistical methods.